2018
DOI: 10.1007/s12034-018-1589-z
|View full text |Cite
|
Sign up to set email alerts
|

Novel dental nanocomposites: fabrication and investigation of their physicochemical, mechanical and biological properties

Abstract: The aim of this study was to investigate biological, physicochemical and mechanical characteristics of a series of novel dental restorative nanocomposites that comprise dendritic methacrylate end-caped monomers, triethylene glycol dimethacrylate (TEGDMA; as diluting monomer) and modified silica nanoparticles (M-SiO 2 ; as inorganic filler). The cytotoxicity effects of the monomers and fabricated nanocomposites were examined against NIH3T3 cells (the standard fibroblast cell line) through MTT and trypan blue ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The results showed that dental composites based on DHMAI possibly enhanced dental composite longevity [ 79 ]. Jaymand et al conducted a series of studies on multi-functional dendritic monomers and found that they can be used to improve the crosslinking degree and performance of resins [ 84 , 85 , 86 , 87 ]. Wang et al synthesized a novel tetrafunctional methacrylate quaternary ammonium salt monomer (TMQA).…”
Section: Current Antimicrobial Strategies Of Resin Compositesmentioning
confidence: 99%
“…The results showed that dental composites based on DHMAI possibly enhanced dental composite longevity [ 79 ]. Jaymand et al conducted a series of studies on multi-functional dendritic monomers and found that they can be used to improve the crosslinking degree and performance of resins [ 84 , 85 , 86 , 87 ]. Wang et al synthesized a novel tetrafunctional methacrylate quaternary ammonium salt monomer (TMQA).…”
Section: Current Antimicrobial Strategies Of Resin Compositesmentioning
confidence: 99%